From bare to birch : large-scale ecosystem restoration in Iceland - Orradottir, Berglind, (SAGE business cases, 2019)
The case of Hekluskógar (meaning "Hekla woodlands") in South Iceland examines how to transition from barren desertified land to a resilient and healthy woodland that can provide ecosystem services to the people in the area and beyond. The case provides a thorough description and background of the many components involved in the largest reforestation project in Europe as of 2018.